LINGUOCULTURAL AND COGNITIVE FEATURES OF THE REALIST PERIOD IN ELIZABETH GASKELL’S “NORTH AND SOUTH” AND CHARLES DICKENS’S “HARD TIMES” - Kuldoshov Uktamjon Urozovich,Radjapova Gavkhar Kurbonovna (International Journal of Literature and Language Studies, 2026)
This paper explores the linguocultural and cognitive features in depicting the XIX century realist period in Charles Dickens’s Hard Times and Elizabeth Gaskell’s North and South. The research focuses on how linguistic expressions, conceptual metaphors and narrative strategies shape cultural perceptions and cognitive models in those novels. The paper applies linguocultural analysis to identify key concepts, such as, fact and fancy, and north and south. At the same time, a cognitive linguistic approach is used to examine character development and conceptual transformations. The findings reveal that both novels serve as linguistic and cognitive representations of industrial society, reflecting contemporary ideological conflicts through character discourse and narrative structure